Kainfortællingen i antikke oversættelser og fortolkninger - Harritsø, Lizette (Dansk Teologisk Tidsskrift, 2012)
Today Cain and Abel are considered the personifi cation of evil itself and the saintlike innocent victim, respectively. The third character of the narrative, Yahweh, seems to be forgotten in the interpretation of the story. He is the one who, by rejecting Cain’s offering, infl ames the anger in him, leading to the fratricide. The story of Cain and Abel as presented in the masoretic version of Genesis 4:1-16 is an ambiguous and versatile story, where Yahweh is presented as a somewhat unjust and passionate God. Cain is portrayed as a facetted human being containing both good and evil. Abel’s character, on the other hand, is barely described. In spite of the fact that the original masoretic version of the narrative does not support the interpretation mentioned above, this interpretation is predominant in contemporary consciousness.